Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Loyalitas Konsumen di Mamayu Resto Kota Solok (International Forum of Researchers and Lecturers, 2024)
This research is motivated by several problems. The aim of this research is to analyze the influence of product quality and service quality on consumer loyalty at Mamayu Resto, Solok City. The type of research used in this research is descriptive with quantitative data. The type of data used in this research is primary data. The population of this research is visitors who come to Mamayu Resto, Solok City. The research sample consisted of 93 consumers with a sampling technique using non-probability sampling. The data collection technique was carried out using a questionnaire with a Likert scale which had been tested for validity and reliability. Data from this research were processed using SPSS 25.00. The results of this research show that the product quality variable shows the sufficient category, with a percentage of 46.24%. The service quality variable shows the sufficient category, with a percentage of 59.14%. The consumer loyalty variable shows the sufficient category, with a percentage of 51.61%. The variables product quality and service quality on consumer loyalty have an influence of 13.8% and 86.2% are influenced by several other factors.